Sexual Dimorphism on Growth Hormone Secretion after Oral Glucose Administration - Outeiriño-Blanco, E.; Garcia-Buela, J.; Sangiao-Alvarellos, S.; Brandón, I.; Pena, L.; Pertega-Diaz, S.; Martinez, T.; Cordido, F. (Hormone and Metabolic Research, 2012)
Sexual dimorphism of GH secretion is unclear in humans. There is evidence that oral glucose (OG) administration initially decreases and subsequently stimulates GH secretion. Our aim was to study fasting GH concentrations and their response to OG administration in obese and healthy women and men, in order to elucidate the mechanism of sexual dimorphism of GH secretion and the possible contribution of ghrelin. We selected 33 women and 11 men as obese and healthy subjects. After an overnight fast, 75 g of oral glucose were administered; glucose, insulin, ghrelin, and PYY1–36 were obtained at baseline and during 300 min. Fasting GH (μg/l) was higher in women than men; 1.3±0.3 vs. 0.2±0.1, p=0.009, for women and men, respectively. The area under the curve between 0 and 150 min (AUC) of GH (μg/l · min) was higher in women than men; 98.2±25.9 vs. 41.5±28.6, p=0.002, for women and men, respectively. The AUC of total ghrelin (pg/ml · min, mean±SEM) between 0 and 150 min was borderline and significantly higher in women than men; 128 562.3±8 335.9 vs. 98 839.1±7 668.6, p=0.069, for women and men, respectively. Several initial time points were higher in women than men. Glucose, insulin, and PYY1–36 were similar in women and men after OG. There were significant correlations between indices of post-oral glucose GH and ghrelin secretion. Fasting and initial GH secretion is higher in women than men, in contrast to peak and late GH secretion, which is similar in both cases. Sexual dimorphism in the regulation of GH secretion probably involves ghrelin.
Keywords: GH; ghrelin; oral glucose; sexual dimorphism